PENGARUH MODEL PEMBELAJARAN CORE TERHADAP PEMAHAMAN KONSEP PESERTA DIDIK PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X MIPA SMA NEGERI 1 KAMPAR TIMUR - Siti Aica; Susilawati Susilawati; Maria Erna (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2019)
The aim of this research is to know the effect of CORE (Connecting, Organizing, Reflecting and Extending) learning models to students concept understanding of atomic strukture. This research is quasi experimental research with a nonequivalent control group. The population in the research is class X SMA Negeri 1 Kampar Timur. The samples in the research was X MIPA 2 as an experimental class and class X MIPA 5 as a control class which was determined randomly. The experimental class was treated with the implementation of CORE learning model while the control class with a scientific approach. Data was collected using essay test instruments. The data obtained from test were analyzed descriptively and statistically by the test-t right side. The results of data analysis obtained tcount = 5,63 and ttable = 1,66 with α = 0,05, dk = 74. Tcount > ttable is 5,63 > 1,66 meaning that the implementation of CORE learning model can improve students concept understanding on the subject of atomic structure in the class X MIPA SMA Negeri 1 Kampar Timur. Criteria students concept understanding in the experimental class with an average N-gain of 0,80 while the average N-gain in the control class is 0,69.